2014
DOI: 10.4103/2156-7514.133258
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of CBCT for Aggressive Periodontitis

Abstract: Cone beam computed tomography (CBCT) is an indispensable diagnostic imaging tool for dento-alveolar examination. CBCT scanning has become a valuable imaging modality in the field of Periodontology for the detection of very small osseous defects. A patient reported to the department of Periodontology with a complaint of loose teeth. Clinical and direct digital radiographic (DDR) examination revealed advanced periodontal destruction, but failed to diagnose the morphology of generalized osseous defects, around al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 6 publications
0
17
0
5
Order By: Relevance
“…Both X-rays and cone beam computed tomography yield information only on vertical and horizontal bone atrophies. While cone beam computed tomography provides more information than periapical X-rays [29], it cannot be used for regular periodontal checkups because of the high doses of radiation required for a proper evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Both X-rays and cone beam computed tomography yield information only on vertical and horizontal bone atrophies. While cone beam computed tomography provides more information than periapical X-rays [29], it cannot be used for regular periodontal checkups because of the high doses of radiation required for a proper evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…CBCT has been shown to be a reliable imaging technique in evaluating the maxillofacial area for oral and periodontal surgeries, dental implant planning and endodontic treatment . CBCT has shown greater diagnostic accuracy in detecting periodontal defects when compared to digital intraoral radiography . Clinical studies showed that CBCT is highly accurate in measuring periodontal bony defects, relative to the gold standard, direct probing (bone sounding) in chronic and aggressive periodontitis .…”
Section: Periodontal Pocket Imaging Technologiesmentioning
confidence: 99%
“…Another study reported that CBCT can successfully provide accurate and high‐quality radiographic images for visualizing the periodontal ligament space . Thus, CBCT has been found to be a useful adjunct for periodontal diagnosis and treatment planning . However, CBCT has mostly been limited to imaging hard tissue due to the low contrast resolution of soft tissue .…”
Section: Periodontal Pocket Imaging Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Em Periodontia, a investigação clínica relativa a medição linear de defeitos intraósseos periodontais por TCFC ainda não é uma rotina e existem poucos relatos. 7,8 As radiografias periapicais, interproximais e panorâmicas são frequentemente empregadas para analisar e diagnosticar níveis ósseos periodontais, no entanto, fornecem apenas uma imagem bidimensional e podem depreciar o real aspecto e profundidade do defeito ósseo. A geometria de projeção do feixe de raios X, por muitas vezes, causa distorção e aumento da imagem, o que dificulta a obtenção de uma análise fidedigna da crista óssea alveolar.…”
Section: Revisão De Literaturaunclassified